Evaluating an incobotulinumtoxinA and Cohesive Polydensified Matrix® hyaluronic acid filler combination to treat moderate‐to‐severe periorbital and perioral rhytids. (26th October 2020) - Barbarino, Sheila C.; Woodward, Julie A.; Levine, Jennifer; Fezza, John
Abstract: Aim: To evaluate the effectiveness of treating mimetic facial lines with an incobotulinumtoxinA (INCO) and Cohesive Polydensified Matrix ® hyaluronic acid (CPM‐HA) combination. Methods: Subjects with moderate‐to‐severe lateral periorbital lines (LPL) and perioral lines at rest according to Merz Aesthetics Scales ™ received 10 U of INCO/eye and up to 10 U to the perioral area. This was followed by intradermal injection of 1‐3 cc CPM‐HA to the same lines. Primary outcomes were physician‐ and subject‐rated improvement at 1 month using the Global Aesthetic Improvement Scale (GAIS) and changes in line severity using the Merz Aesthetics Scales ™ . Results: The study included 10 women aged 42‐74 years with moderate‐to‐severe LPL and perioral lines at baseline. At 1 month, treating physician GAIS scores indicated 45.0% of subjects were very much improved and 52.5% much improved; 75% remained at least improved at 6 months. Subject GAIS results indicated 7 women rated themselves as very much improved and 3 as much improved. For LPL, improvements of ≥1‐point on the Merz Aesthetics Scales ™ compared with baseline were seen at 1, 3, and 6 months in 86.8%, 74.3%, and 65.8% of subjects, respectively. For perioral lines, improvements of ≥1‐point were observed for 89.2%, 86.5%, and 73.0% at 1, 3, and 6 months, respectively. No treatment‐related adverse events were observed. Conclusions: Combined INCO/CPM‐HA filler in individuals with moderate‐to‐severe LPL and perioral lines was effective at improving overall appearance and reducing line severity in two highly mobile facial areas that are the first to show lines of aging.